2020
DOI: 10.1177/0268355520949775
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in patients with lipedema 4, 8 and 12 years after liposuction

Abstract: Background Long-term results following liposuction in patients with lipedema were available only for an average period of 8 years. Objective To find out whether the improvements persist for a further 4 years. Methods In 60 patients with lipedema a single-centre study with a mail questionnaire – often in combination with clinical controls – was performed after an average period of 12 years following liposuction(s). All patients in this group had already been surveyed 4 and 8 years after surgery. Results Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 11 publications
1
24
0
4
Order By: Relevance
“…72 2.0 Medical treatment 2.1 Signs and symptoms of lipedema can be treated to maintain and improve quality of life including pain, edema, and mobility; earlier treatment provides better results. 17,42,64,66,73 (B) 2.2 A Complete patient evaluation and assessment identifies impairments that can be addressed with medications, therapy, or referrals to other providers (Table 1). 11,17 (C) 2.3 Barriers to treatment of lipedema include difficulty of self-care, mobility limitations, social stigma attached to increased body size and physical limitations, anxiety, depression, 65 lack of social support, 12 availability of knowledgeable healthcare providers and affordability of services and limitations of some non-surgical treatments to reduce lipedema tissue.…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…72 2.0 Medical treatment 2.1 Signs and symptoms of lipedema can be treated to maintain and improve quality of life including pain, edema, and mobility; earlier treatment provides better results. 17,42,64,66,73 (B) 2.2 A Complete patient evaluation and assessment identifies impairments that can be addressed with medications, therapy, or referrals to other providers (Table 1). 11,17 (C) 2.3 Barriers to treatment of lipedema include difficulty of self-care, mobility limitations, social stigma attached to increased body size and physical limitations, anxiety, depression, 65 lack of social support, 12 availability of knowledgeable healthcare providers and affordability of services and limitations of some non-surgical treatments to reduce lipedema tissue.…”
Section: (B)mentioning
confidence: 99%
“…Lipedema reduction surgery may be less effective in advanced stages of lipedema 66 and in women with lipedema and severe obesity [110][111][112]119 although recent data demonstrate a greater reduction of symptoms in more advanced cases. 73 Surgery may involve multiple procedures, however, the optimal time between procedures is unknown. (B) 4.17.…”
Section: (A)mentioning
confidence: 99%
“…Baumgartner et al followed 85 women with lipedema 4, 8 and 12 years after liposuction and found that benefits in pain, restriction of movement, edema, quality of life, and bruising at 4 years after liposuction persisted up to 12 years. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Pain in the adipose tissue is one of the most common symptoms, which causes a lot of limitation in everyday and professional life [ 12 ]. Patients report additional symptoms in the affected areas, such as bruising, sensitivity to touch, feeling of tension, heavy and tired limbs and aesthetic impairment ( Table 1 ) [ 13 , 14 , 15 , 16 ]. Affected patients usually recognize the first symptoms like enlargement of the legs during adolescence [ 3 , 7 , 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current literature suggests that liposuction may be a promising approach as an invasive treatment modality in terms of pain reduction and increase in the quality of life [ 13 , 14 , 15 , 16 , 23 ].…”
Section: Introductionmentioning
confidence: 99%